Exploratory examples for real analysis - Snow, Joanne E. (Mathematical Association of America, 2003)
Contains supplementary exercises and projects designed to facilitate students' understanding of the fundamental concepts in real analysis, a subject notoriously hard for beginners. The exercises can be used in a number of ways: to motivate a lecture; to serve as a basis for in-class activities; in lab sessions where students work in small groups and submit reports of their investigations.